Nested-list Approach for the Stageless Evaluation of a Vector Preisach Model based on Rotational Operators - Nierla, Michael; Rupitsch, Stefan; Kaltenbacher, Manfred (AMA Conferences 2017 – SENSOR 2017 and IRS2 2017, 2017)
The Everett function is a widely used tool to evaluate the output of scalar Preisach hysteresis operators. Compared to a matrix-based implementation, the Everett function does not only allow a stageless evaluation of the switching state but, furthermore, reduces the required storage to a single list of dominant input minima and maxima. To deal with magnetic fields that change direction over time, a vector extension of the scalar Preisach model based on rotational operators can be utilized. This straight-forward extension enables an efficient description of vector hysteresis phenomena. Due to the dependency between the newly added rotational operator and the original switching operator, neither the usage of a single list nor the direct application of the Everett function is possible. In this contribution, we propose a nested-list data structure for the vector Preisach model based on rotational operators. Exploiting this data structure allows the usage of an adapted Everett function and, thus, an efficient, stageless representation of both the rotational operator as well as the switching operator.
Keywords: Everett Function; Hysteresis Modeling; Vector Preisach